East Asia the great tradition - Reischauer, Edwin O. (Houghton Miffin, 1960)
It is the purpose of this book to trace the growth and development of East Asian civilization-namely that of China, Japan, Korea and contiguous areas-from its beginnings in North China up to the first half of the 19th century,...